The Impact of Social and Personality Competence on the Professional Competence of Elementary School Teachers with Organizational Culture as a Moderator - Ryan Pratiwa Putra; Rendi Kurniawan; Lina Marlina; Hamidah Hamidah; Mutoharoh Mutoharoh (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2026)
Every teacher must master all dimensions of competency in an integrative manner, but the reality in the field often shows sharp gaps. Professional competence does not stand alone but is rather the result of the accumulation of various other dimensions of ability, including social competence and personality competence. The main objective of this study is to empirically analyze the influence of social competence and personality competence on teacher professional competence, as well as to examine the role of organizational culture as a moderating variable in this relationship. This quantitative research with a causal associative design was conducted systematically in Serang City during the first and second weeks of May 2026. The research population comprised elementary school teachers, from which a sample of 117 respondents was selected using a combination of convenience and quota sampling techniques. Criteria for selection required a minimum Bachelor's degree (S1) and two years of service to ensure institutional adaptation. Data were collected via an anonymous online survey utilizing structured five-point Likert scale questionnaires, which were pre-tested and declared highly reliable (Cronbach's Alpha > 0.80). The gathered data were then processed using descriptive statistics and inferential analysis through Moderated Regression Analysis (MRA). The results show that personality competence and social competence are significant determinants that have a positive and significant direct influence on improving the professional competence of elementary school teachers. Statistical estimation reveals that social competence exerts the most dominant direct impact (β = 0.383, p < 0.001), followed by personality competence (β = 0.228, p = 0.021), and a direct effect from organizational culture (β = 0.267, p = 0.002). The overall model demonstrates robust predictive validity (R2 = 0.430, F-test p < 0.001). On the other hand, organizational culture has not been proven to significantly moderate the relationship between individual competencies and professional competence, indicated by non-significant interaction coefficients for both personality (p = 0.164) and social dynamics (p = 0.352). This implies that teacher professionalism operates with high intrinsic autonomy, meaning highly competent individuals will maintain stable professional execution regardless of environmental fluctuations.